Laryngoscopy evaluation protocol for the differentiation of essential and dystonic voice tremor - Bruno Teixeira de Moraes; Noemi Grigoletto de Biase (Brazilian Journal of Otorhinolaryngology, 2016)
ABSTRACT INTRODUCTION: Although syndromes that cause voice tremor have singular characteristics, the differential diagnosis of these diseases is a challenge because of the overlap of the existing signs and symptoms. OBJECTIVE: To develop a task-specific protocol to assess voice tremor by means of nasofibrolaryngoscopy and to identify those tasks that can distinguish between essential and dystonic tremor syndromes. METHODS: Cross-sectional study. The transnasal fiberoptic laryngoscopy protocol, which consisted of the assessment of palate, pharynx and larynx tremor during the performance of several vocal and non-vocal tasks with distinct phenomenological characteristics, was applied to 19 patients with voice tremor. Patients were diagnosed with essential or dystonic tremor according to the phenomenological characterization of each group. Once they were classified, the tasks associated with the presence of tremor in each syndrome were identified. RESULTS: The tasks that significantly contributed to the differential diagnosis between essential and dystonic tremor were /s/ production, continuous whistling and reduction of tremor in falsetto. These tasks were phenomenologically different with respect to the presence of tremor in the two syndromes. CONCLUSION: The protocol of specific tasks by means of transnasal fiberoptic laryngoscopy is a viable method to differentiate between essential and dystonic voice tremor syndromes through the following tasks: /s/ production, continuous whistling and reduction of tremor in falsetto.